we are given
[tex]f(x)=5[/tex]
[tex]g(x)=\sqrt{x+2}[/tex]
(8)
[tex](f+g)(x)=f(x)+g(x)[/tex]
we can plug it
[tex](f+g)(x)=5+\sqrt{x+2}[/tex]
(9)
[tex](f-g)(x)=f(x)-g(x)[/tex]
we can plug it
[tex](f-g)(x)=5-\sqrt{x+2}[/tex]
(10)
[tex](f*g)(x)=f(x)*g(x)[/tex]
we can plug it
[tex](f*g)(x)=5\sqrt{x+2}[/tex]
(11)
[tex](\frac{f}{g} )(x)=\frac{f(x)}{g(x)}[/tex]
we can plug it
[tex](\frac{f}{g} )(x)=\frac{5}{\sqrt{x+2}}[/tex]
(12)
[tex](\frac{g}{f} )(x)=\frac{g(x)}{f(x)}[/tex]
we can plug it
[tex](\frac{g}{f} )(x)=\frac{\sqrt{x+2}}{5}[/tex]
(13)
[tex](fog)(x)=f(g(x))[/tex]
[tex]f(x)=5[/tex]
we can replace g(x)
we get
[tex](fog)(x)=5[/tex]
(14)
[tex](gof)(x)=g(f(x))[/tex]
[tex]f(x)=5[/tex]
we can replace f(x)
[tex](gof)(x)=\sqrt{f(x)+2}[/tex]
we get
[tex](gof)(x)=\sqrt{5+2}[/tex]
[tex](gof)(x)=\sqrt{7}[/tex]